2016
DOI: 10.1140/epjb/e2016-60956-2
|View full text |Cite
|
Sign up to set email alerts
|

Global and partitioned reconstructions of undirected complex networks

Abstract: Abstract. It is a significant challenge to predict the network topology from a small amount of dynamical observations. Different from the usual framework of the node-based reconstruction, two optimization approaches (i.e., the global and partitioned reconstructions) are proposed to infer the structure of undirected networks from dynamics. These approaches are applied to evolutionary games occurring on both homogeneous and heterogeneous networks via compressed sensing, which can more efficiently achieve higher … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…[15] Nevertheless, the application of phosphor ceramic is limited because of the rigorous (hightemperature, high vacuum), complex and costly preparation process. [16,17] PiG (dispersing phosphors in glass matrix) is regarded as an ideal material for LDs owing to its adjustable luminescence performance and low cost. [18,19] Zhu et al reported CaAlSiN 3 : Eu 2+ PiG with a TC of 1.12 W m −1 K −1 at room temperature, and a ST of 0.5 W mm −2 under blue laser irradiation.…”
Section: Doi: 101002/lpor202200585mentioning
confidence: 99%
“…[15] Nevertheless, the application of phosphor ceramic is limited because of the rigorous (hightemperature, high vacuum), complex and costly preparation process. [16,17] PiG (dispersing phosphors in glass matrix) is regarded as an ideal material for LDs owing to its adjustable luminescence performance and low cost. [18,19] Zhu et al reported CaAlSiN 3 : Eu 2+ PiG with a TC of 1.12 W m −1 K −1 at room temperature, and a ST of 0.5 W mm −2 under blue laser irradiation.…”
Section: Doi: 101002/lpor202200585mentioning
confidence: 99%
“…The other method uses accessible structure information to reconstruct a class of networks with evolutionary games [18,19]. Such model, known as compressive sensing reconstruction model (CSR), is initially proposed to solve the problems of global network reconstruction [20][21][22]. The CSR method provides theoretical framework to dealing with networks purely from measured time-series information.…”
Section: Introductionmentioning
confidence: 99%